Astrocytes acquire morphological and functional characteristics of ependymal cells following disruption of ependyma in hydrocephalus - Roales-Buján, Ruth; Páez-González, Patricia; Guerra, Montserrat; Rodriguez, Sara; Vío, Karin; Ho-Plágaro, Ailec; García-Bonilla, María; Rodríguez-Pérez, Luis Manuel; Domínguez-Pinos, Dolores; Martín Rodriguez, Esteban; Pérez-Figárez, José Manuel; Jiménez-Lara, Antonio Jesús (Springer Nature Limited, 2012)
Hydrocephalic hyh mutant mice undergo a programmed loss of the neuroepithelium/ependyma followed by a reaction of periventricular astrocytes, which form a new cell layer covering the denuded ventricular surface. We present a comparative morphological and functional study of the newly formed layer of astrocytes and the multiciliated ependyma of hyh mice. Transmission electron microscopy, immunocytochemistry for junction proteins (N-cadherin, connexin 43) and proteins involved in permeability (aquaporin 4) and endocytosis (caveolin-1, EEA1) were used. Horseradish peroxidase (HRP) and lanthanum nitrate were used to trace the intracellular and paracellular transport routes. The astrocyte layer shares several cytological features with the normal multiciliated ependyma, such as numerous microvilli projected into the ventricle, extensive cell-cell interdigitations and connexin 43-based gap junctions, suggesting that these astrocytes are coupled to play an unknown function as a cell layer. The ependyma and the astrocyte layers also share transport properties: (1) high expression of aquaporin 4, caveolin-1 and the endosome marker EEA1; (2) internalization into endocytic vesicles and early endosomes of HRP injected into the ventricle; (3) and a similar paracellular route of molecules moving between CSF, the subependymal neuropile and the pericapillary space, as shown by lanthanum nitrate and HRP. A parallel analysis performed in human hydrocephalic foetuses indicated that a similar phenomenon would occur in humans. We suggest that in foetal-onset hydrocephalus, the astrocyte assembly at the denuded ventricular walls functions as a CSF-brain barrier involved in water and solute transport, thus contributing to re-establish lost functions at the brain parenchyma-CSF interphase.
Keywords: Hidrocefalia; Cerebrospinal fluid; Ependyma disruption; Astrocyte reaction; Barrier properties; Permeability; Transport; Human; Congenital hydrocephalus; Hyh mice